2019
DOI: 10.1111/jmi.12856
|View full text |Cite
|
Sign up to set email alerts
|

A study on the indexing method of the electron backscatter diffraction pattern assisted by the Kikuchi bandwidth

Abstract: In this study, a new method is established for indexing electron backscatter diffraction (EBSD) patterns assisted by the Kikuchi bandwidth. This method utilises both interplanar angles and interplanar spacings to determine the Miller indices of the Kikuchi bands in EBSD patterns to improve the efficiency and precision of indexing in the EBSD system. Two samples of single-crystal silicon were investigated to validate the method based on (a) the detection of the edges of the EBSD Kikuchi bands and (b) the calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…The lengths of reciprocal‐lattice vectors were corrected, and the RLVs, after correction were used for calculating lattice spacing. Compared to our previous method of calculating the lattice spacing by bandwidth, 19 the new method significantly improved the calculation accuracy without considerably increasing the computation required. The results of five Kikuchi patterns with different clarity showed that this new method reduced the average error of interplanar spacings by 50.611% and achieved an average accuracy of 1.644% for lattice spacing.…”
Section: Introductionmentioning
confidence: 94%
“…The lengths of reciprocal‐lattice vectors were corrected, and the RLVs, after correction were used for calculating lattice spacing. Compared to our previous method of calculating the lattice spacing by bandwidth, 19 the new method significantly improved the calculation accuracy without considerably increasing the computation required. The results of five Kikuchi patterns with different clarity showed that this new method reduced the average error of interplanar spacings by 50.611% and achieved an average accuracy of 1.644% for lattice spacing.…”
Section: Introductionmentioning
confidence: 94%
“…Any manual definition of band edges is a highly individual and therefore subjective and non-reproducible decision (Li & Han, 2015;Oishi-Tomiyasu et al, 2021). Peng et al (2020) used the band edges themselves to optimize the trace positions of the diffracting lattice planes required for pattern indexing. In the present work we use the first derivative, successfully introduced already by Alam et al (1954), Shorter & Dobson (1981) and Saowadee et al (2017), for an approximation of hkl to determine the mean lattice parameter a from them.…”
Section: Band Widthsmentioning
confidence: 99%
“…电子背散射衍射(EBSD)作为一种相对较新的 显微结构分析手段,可以在较大范围内提供材料的 取向、织构、相鉴定及含量分布等晶体学统计性信 息 [1][2][3][4] ,为无机材料制备工艺的改善、微结构调控及 性能优化提供了可靠的科学依据。Fang 等 [5] 通过 EBSD 技术对梯度纳米(GNG)金属铜进行表征, 为解释其拉伸变形的机理提供了重要显微结构证据。 EBSD 还是研究涂层内部残余应力分布的最佳显微 结构分析手段,为研究热障涂层的服役失效行为提 供了重要支撑。EBSD 提供的所有晶体学信息都依 赖对菊池衍射花样的分析 [6] ,菊池花样直观反映材 料内部微观结构,其中,菊池带对应不同指数的晶 面,菊池带的交点即菊池极代表晶带轴 [4] [7] 尝试利用对称性进行相鉴定,但 因为晶面间距计算误差较大,只能依靠肉眼在菊池 花样中识别对称轴,容易误判。通过菊池带宽度计 算晶面间距的误差通常较大(5%~20%) [7][8] ,这是 用菊池花样进行对称性分析的最大难点。我们前期 工作对晶面间距进行了准确测量,平均相对误差为 2.6% [9] ,为准确识别对称轴奠定了基础,还可区分 非对称轴。对 Si 单晶菊池花样的分析发现了类似三 次轴的非对称轴,计算晶面间距发现,菊池带并不 属于同一晶面族,不满足三次轴的条件,这是肉眼 识别很容易误判的。晶面夹角可通过三维空间矢量 计算获得 [10]…”
unclassified